One-hour plasma glucose as a long-term predictor of cardiovascular events and all-cause mortality in a Chinese older male population without diabetes: A 20-year retrospective and prospective study - Rong, Lingjun; Cheng, Xiaoling; Yang, Zaigang; Gong, Yanping; Li, Chunlin; Yan, Shuangtong; Sun, Banruo (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between one-hour plasma glucose (1h-PG) and the incidence of type 2 diabetes has been investigated in previous studies. However, the predictive value of 1h-PG for the risk of cardiovascular disease (CVD) and all-cause mortality, especially in older Asians, has been investigated in only a few studies. Therefore, the influence of 1h-PG on the incidence of CVD and mortality was evaluated in the present study. Methods: The participants were recruited from the Chinese People’s Liberation Army General Hospital, and were categorized into 1h-PG tertiles. The primary outcomes were all-cause mortality, myocardial infarction, unstable angina, and stroke. Multivariate adjusted Cox proportional hazard regression models were performed to examine the association between risk factors and outcomes and to estimate the risk of CVD and all-cause mortality based on 1h-PG. Results: The study included 862 male participants. Median age was 74.0 (25th–75th percentile: 68.0–79.0) years. There were 480 CVD events and 191 deaths during 15,527 person-years of follow-up. The adjusted hazard ratio (HR) of 1h-PG as a continuous variable was 1.097 (95% CI 1.027–1.172; P = 0.006) for CVD events and 1.196 (95% CI 1.115-1.281; P < 0.001) for higher risk of mortality. When compared with the lowest 1h-PG tertile, the other tertiles were associated with CVD events (HR 1.464, 95% CI 1.031–2.080; P = 0.033 and HR 1.538, 95% CI 1.092–2.166; P = 0.014, for tertile 2 and tertile 3 compared with tertile 1, respectively), and the highest 1h-PG tertile had a significantly higher risk of mortality (HR 2.384, 95% CI 1.631-3.485; P < 0.001) after full adjustment. Conclusion: Higher 1h-PG is associated with an increased risk of all-cause mortality and CVD. 1h-PG might be a better predictor of CVD than 2h-PG in older adults.